Determination of Damsin, Glycyrrhizin, Khellin and Azulene in the Traditional Egyptian Medicinal Preparation Sekem Renal Herbal Tea by High Performance Liquid Chromatography - El-Azizi, Mohamed; D. El-Gindi, Omayma; Samir, Abear; I. Khalifa, Taha (Asian Journal of Chemistry, 2010)
High-performance liquid chromatography was employed to determine the contents of several marker substances such as damsin, glycyrrhizin, khellin and azulene in Sekem renal herbal tea. The separation was performed on a microbondapack C18 column with 10 μn particle diameter and 30 cm length using methanol-water (93 : 7) as a mobile phase at flow rate 0.25 mL/min with detection at 254 nm; also this condition was used to develop fingerprint chromatogram for the alcoholic extract of the renal tea to be used as a rapid method for its quality control. The accuracy and precision (relative standard deviation) of the method were in the ranges 68–100% and 1.5–8.8% respectively.